Detecting changing river temperatures in England and Wales. Issue 5 (20th March 2014) - Orr, Harriet G.; Simpson, Gavin L.; des Clers, Sophie; Watts, Glenn; Hughes, Mike; Hannaford, Jamie; Dunbar, Michael J.; Laizé, Cédric L. R.; Wilby, Rob L.; Battarbee, Richard W.; Evans, Rob
Abstract Changes in water temperature can have important consequences for aquatic ecosystems, with some species being sensitive even to small shifts in temperature during some or all of their life cycle. While many studies report increasing regional and global air temperatures, evidence of changes in river water temperature has, thus far, been site specific and often from sites heavily influenced by human activities that themselves could lead to warming. Here we present a tiered assessment of changing river water temperature covering England and Wales with data from 2773 locations. We use novel statistical approaches to detect trends in irregularly sampled spot measurements taken between 1990 and 2006. During this 17‐year period, on average, mean water temperature increased by 0.03 °C per year (±0.002 °C), and positive changes in water temperature were observed at 2385 (86%) sites. Examination of catchments where there has been limited human influence on hydrological response shows that changes in river flow have had little influence on these water temperature trends. In the absence of other systematic influences on water temperature, it is inferred that anthropogenically driven climate change is driving some of this trend in water temperature. © 2014 The Authors. Hydrological Processes published by John Wiley & Sons Ltd.